2015
DOI: 10.1177/1477153515577851
|View full text |Cite
|
Sign up to set email alerts
|

Glare and cognitive performance in screen work in the presence of sunlight

Abstract: Research concerning the effects of glare on distraction is scarce. We designed a 2 Â 2 repeated measures experiment (n ¼ 32) in order to examine the influence of a large area glare source and glare sensitivity on reported discomfort glare and cognitive performance. Daylight glare probability was the within-subjects variable and glare sensitivity was the between-subjects variable. We found a statistically significant difference in glare sensation votes between scenarios, without statistically significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Using glare sensation vote and yes/no self-evaluation of sensitivity could mitigate results. Rodriguez et al 26 found no difference, although they did in a previous study. 27 Van Den Wymelenberg 10 measured self-reported sensitivity on a seven-point scale and found low correlation (r 2 = 0,04) with measured sensitivity to brightness but noted that those who are very sensitive tend to select dimmer conditions compared with those who are least sensitive.…”
Section: Other Physiological Factorsmentioning
confidence: 75%
“…Using glare sensation vote and yes/no self-evaluation of sensitivity could mitigate results. Rodriguez et al 26 found no difference, although they did in a previous study. 27 Van Den Wymelenberg 10 measured self-reported sensitivity on a seven-point scale and found low correlation (r 2 = 0,04) with measured sensitivity to brightness but noted that those who are very sensitive tend to select dimmer conditions compared with those who are least sensitive.…”
Section: Other Physiological Factorsmentioning
confidence: 75%
“…This result is in line with findings of previous studies suggesting that lower illuminance levels during morning hours promote higher performance in tasks associated with sustained attention. 26,27 S OFF setting resulted in lower illuminance range and high daylight variation which was two times higher than S ON setting. Considering the southeast orientation of workstation receiving morning sunlight more intensely than in the afternoon, therefore, in such cases, the use of solar shading systems can be very useful especially during morning hours for increasing work productivity as well as minimizing accidents in such VDT works requiring high attention.…”
Section: Discussionmentioning
confidence: 89%
“…Studies concerning the effect of daylighting on cognitive task performance in work environments however are still very scarce although daylight is recognized as the most preferred in working spaces 22 for being more efficient in visual, physiological and psychological functions. [23][24][25] Of the available literature that dealt with the impact of daylight on cognitive performance exclusively during VDT work, Rodriguez et al 26 measured attention and working memory in two different scenarios (a neutral environment and a glare demanding environment) in a rotatable experimental module where participants performed two different computer-based cognitive tasks. Each experimental session lasted about 30 min and data collection took 40 mornings with a total number of 32 participants.…”
Section: Introductionmentioning
confidence: 99%
“…This could be rectified by substituting imperceptible with another scale anchor that clearly communicates that no glare is present. The use of unnoticeable by Rodriguez et al (2015) as the lowest response scale point improves but does not entirely remove this issue. The use of extended behaviorally anchored definitions is likely to provide more reliable judgments; however, including definitions may not be feasible or desirable in a field setting.…”
Section: Limitationsmentioning
confidence: 98%